Effects of sulphate deposits on corrosion behaviour of Ni-base alloys in wet CO2 gas at 750 °C. (1st April 2021) - Xie, Yun; Cai, Yuchen; Zhang, Jianqiang; Gleeson, Brian; Young, David J.
Abstract: The corrosion performance of several model and commercial Ni-base alloys, with 20 − 25 wt % Cr, in CO2 -H2 O gases at 750 °C with and without sulphate deposits was examined. In the absence of sulphate deposits, commercial NiCoCrAl alloy and Alloy 625 formed chromia-rich scales, but model alloys Ni-25Cr and Ni-25Cr-2Mn-1Si did not. Wagner's theory was employed to interpret this different behaviour in terms of chromia layer formation. With the deposition of sulphate, the four alloys underwent internal sulphidation to different extents. The commercial NiCoCrAl alloy in particular experienced extensive degradation due to acidic fluxing of the corrosion scale.